Иванов А.Е. Ученые степени в Российской империи. ХVІІІ в. - Шандра, В. С. (Український історичний журнал, 2025)
Иванов А.Е. Ученые степени в Российской империи. ХVІІІ в. — 1917 г. — М.: Рос. АН, Ин-т рос. истории, 1994. — 198 с.